The Growth response of patin fish (pangasius sp.) To nutrinex enerc supplementation in feed at various dose levelsE LEVELS - Muhammad Gilang Ramadhan; Ren Fitriadi; Agnes Heratri; Maghfira Selia Irawati; Sreshi Asa Mahendra (Journal Of Artha Biological Engineering, 2026)
Optimizing feed utilization is an important strategy in increasing the productivity of Patin Fish (Pangasius sp.) rearing. The addition of multivitamin supplements to feed can increase metabolic efficiency and nutrient utilization, thereby improving fish growth performance. This study aims to evaluate the effects of Nutrinex EnerC supplementation at different doses on the growth performance and feed utilization efficiency of Patin Fish. The study used a Completely Randomized Design (CRD) with three treatments and three replications, namely P1 (0 g/kg feed), P2 (3 g/kg feed), and P3 (6 g/kg feed). Fish were reared in a biofloc system and fed at a feeding rate of 3% of body weight during the maintenance period. The parameters observed included weight growth, length growth, Average Daily Growth (ADG), Specific Growth Rate (SGR), Feed Conversion Ratio (FCR), feed efficiency, and Survival Rate (SR). Data were analyzed using analysis of variance (ANOVA) followed by Tukey's test at a 95% confidence level. The results showed that Nutrinex EnerC supplementation significantly affected weight growth, ADG, SGR, FCR, and feed efficiency (p<0.05), but did not significantly affect length growth and fish survival. The best treatment was obtained at a dose of 6 g/kg feed which resulted in weight growth of 8.87 ± 0.40 g, ADG 0.25 ± 0.01 g/day, SGR 4.84 ± 0.02%/day, FCR 0.54 ± 0.02, and feed efficiency of 186.59 ± 8.50%. The results of this study indicate that Nutrinex EnerC supplementation has the potential to increase feed utilization efficiency and growth performance of Patin Fish in intensive rearing systems.